Confiabilidad en la evaluación de la calidad de exámenes en ciencias de la salud - Jeel Moya-Salazar; Iris J. Baldárrago-Valdivia; María E. Delgado-Díaz; Tatiana M. Erazo; Delsy B. Ortiz; Ericka T. Saboya (Revista Cubana de Medicina Militar)
Confiabilidad en la evaluación de la calidad de exámenes en ciencias de la salud